2017
DOI: 10.1016/j.jasc.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspirates of thyroid microcarcinoma

Abstract: Precis:In our experience, indeterminate diagnoses (FLUS+FN+SM) accounted for the majority (60%) of preoperative FNAs for incidental microcarcinoma (size ≤0.5 cm) when compared to 27% for those of non-incidental microcarcinoma (size >0.5 cm and ≤1 cm) (p<0.05, chi-square test). ABSTRACT: INTRODUCTION:Widespread use of ultrasound allows for detection of smaller thyroid nodules and preoperative evaluation with fine-needle aspiration (FNA). Both incidental and non-incidental microcarcinoma can be found, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…While some authors advocate that FNAB should precede the decision of active surveillance of nodules ≤ 10 mm (11), our study shows that FNAB is frequently caught in default in small nodules. This is consistent with previous reports showing rates as high as 60% of indeterminate cytological diagnosis (Bethesda III, IV, V) for malignant thyroid nodules under 5 mm and 27% for those between 5 and 10 mm have been reported (12). It has also been shown that there are up to 17.8% of non-diagnostic specimens (Bethesda I) in nodules ≤ 10 mm (13), and up to 35.6% in non-palpable nodules under 8 mm (14).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…While some authors advocate that FNAB should precede the decision of active surveillance of nodules ≤ 10 mm (11), our study shows that FNAB is frequently caught in default in small nodules. This is consistent with previous reports showing rates as high as 60% of indeterminate cytological diagnosis (Bethesda III, IV, V) for malignant thyroid nodules under 5 mm and 27% for those between 5 and 10 mm have been reported (12). It has also been shown that there are up to 17.8% of non-diagnostic specimens (Bethesda I) in nodules ≤ 10 mm (13), and up to 35.6% in non-palpable nodules under 8 mm (14).…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, some authors such as P W Rosario et al (11) consider that FNAB should precede the decision of AS of nodules ≤ 10 mm, to avoid repeating US if benign, to prevent the psychological stress of having a presumptive diagnosis of 'cancer' or of a 'nodule with highly suspicious features', or to detect rare cytological variants of cancer that are not candidates for active surveillance. However, rates of non-diagnostic and indeterminate cytological results in sub-centimeter nodules can be as high as 35.6 and 60%, respectively (12,13,14). These suspicious nodules, with no evidence of malignancy, were excluded from previous studies, thus introducing a potential recruitment bias.…”
Section: Introductionmentioning
confidence: 99%